Improved Hybrid Approach for Load Balancing In Virtual Machine - Rao, G.Srinivasa; Anuradha, T (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a term generally used for the delivery of hosted services over the internet. In simple terms can be stated as “PAY-AND-USE Online Software resources”. Cloud computing makes to use the computing resource online. Balancing the load in the cloud is one of the important parameter which is to be focused. Hybrid Approach to Load balancing in Cloud Environment is a combination of two or more algorithms to achieve the betterment in the Cloud Service to the clients. With the observations it looks that RT Hybrid Algorithm would make the improvement for the better implementation.